Analisis Peran CBT terhadap Lingkungan di Desa Wisata Karangrejo - F., Cyrillus Fishio; Cahyanti S, Dhistia; Aulia’i, Iqrima Aurora; Jagad, Lintang Sekar; Kumala, Natalia Citra; Qasamah, Syakira Isyraf (JURNAL NASIONAL PARIWISATA, 2024)
Karangrejo Tourism Village is one of the tourism villages that implements Community-Based Tourism (CBT) as the main strategy in managing and developing local tourism. Through active community involvement in various initiatives such as tour guide services, empowerment through the Sumber Makmur Organic Farmers Association (PPOSM), development of Kampung Organic agrotourism, provision of homestays based on local wisdom, as well as environmental cleaning and education activities, CBT has succeeded in improving economic welfare and maintaining environmental sustainability. This study aims to explore the context of environmental sustainability that arises with tourism using the CBT model. The method used in this study is qualitative-descriptive using primary and secondary data obtained through interviews and document studies by reviewing relevant sources. The data shows that village income reached 2 billion rupiah, reflecting a positive contribution from the implementation of CBT. The success of Karangrejo Village in implementing CBT shows that with the right strategy and strong community participation, community-based tourism can be a model for developing sustainable tourism villages that provide economic, social, and environmental benefits holistically. This study underlines the importance of CBT management in supporting sustainability for the environment and provides recommendations for other regions to develop it.